2017
DOI: 10.56093/ijas.v87i9.74165
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bio-fertilizers and mulching on growth, yield and quality of strawberry (Fragaria × ananassa) cv. Chandler

Abstract: A study was undertaken to examine the efficacy of bio-fertilizers and mulching on growth, yield and quality of strawberry (Fragaria × ananassa Duch.) cv. Chandler during two successive years, i.e. 2012-13 and 2013-14 at Kanpur (Uttar Pradesh), India. The experiment was laid out in randomized block design with three replications and ten treatments. One year old runners were used for planting. Significantly increase in plant height (19.20 and 18.70cm), number of leaves (17.15 and 16.75), number of runners (2.28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…The maximum (28.14 and 27.13) days required to flowering was presented with control (G 0 Z 0 ) during both the years of experiments. These results are also in conformity with the findings of Mukhtar et al [14] in olive and Tripathi and Shukla [15] in strawberry. GA application also enhanced the number of flowers per shoot, might be due to enforcement of photosynthetic and other metabolic activities which lead to increase in various plant metabolites responsible for cell division and cell elongation, photosynthetic activity, respiration as well as growth of plant.…”
Section: Days Required To Floweringsupporting
confidence: 93%
“…The maximum (28.14 and 27.13) days required to flowering was presented with control (G 0 Z 0 ) during both the years of experiments. These results are also in conformity with the findings of Mukhtar et al [14] in olive and Tripathi and Shukla [15] in strawberry. GA application also enhanced the number of flowers per shoot, might be due to enforcement of photosynthetic and other metabolic activities which lead to increase in various plant metabolites responsible for cell division and cell elongation, photosynthetic activity, respiration as well as growth of plant.…”
Section: Days Required To Floweringsupporting
confidence: 93%
“…For instance, when investigating the effect of production systems on strawberry quality, Fan et al (2011) demonstrated that plastic mulch with row covers improved postharvest nutritional value by increasing total phenolic and antioxidant levels (Fan et al, 2011). Other studies have demonstrated that the application of black polythene mulching alone (Bakshi et al, 2014; and in combination with azotobacter bio-fertilization improved total sugar, ascorbic acid, and protein content in strawberries (Tripathi et al, 2017). Moor et al (2004 reported similar increase in vitamin C content with plastic and straw mulch (Moor et al, 2004), while Wang et al (1998) demonstrated accumulation of ascorbic acid, ellagic acid, and carbohydrates in strawberry plants grown using black polyethylene, red polyethylene and straw-vetch mulches (Wang et al, 1998).…”
Section: Mulchingmentioning
confidence: 95%
“…Therefore, the combined use of biofertilizer, Panchagavya, and FYM improved the mango's fruiting characteristics because more food material was accumulated in the trees and was used effectively for the production of fruits. Sau et al [11], Tripathi et al, [12] in strawberry and Tripathi et al, [13] in aonla. The usage of Panchagavya coupled with FYM and biofertilizers resulted in the accumulation of additional food material and its effective utilization for the growth of fruits, which led to the rise in fruit volume.…”
Section: Fruit Volume (Cc)mentioning
confidence: 99%